Diagnosis and Staging of Lymphedema - Greene, Arin K.; Goss, Jeremy A. (Seminars in Plastic Surgery, 2018)
Lymphedema often is confused with other causes of extremity edema and enlargement. Understanding the risk factors and physical examination signs of lymphedema can enable the health care practitioner to accurately diagnose patients ∼90% of the time. Confirmatory diagnosis of the disease is made using lymphoscintigraphy. It is important to correctly diagnose patients with lymphedema so that they can be managed appropriately.
Keywords: extremity; lymphedema; lymphoscintigraphy; diagnosis; staging